2018
DOI: 10.1128/mcb.00446-18
|View full text |Cite
|
Sign up to set email alerts
|

New Player in Endosomal Trafficking: Differential Roles of Smad Anchor for Receptor Activation (SARA) Protein

Abstract: The development and maintenance of multicellular organisms require specialized coordination between external cellular signals and the proteins receiving stimuli and regulating responses. A critical role in the proper functioning of these processes is played by endosomal trafficking, which enables the transport of proteins to targeted sites as well as their return to the plasma membrane through its essential components, the endosomes. During this trafficking, signaling pathways controlling functions related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…In the developing cortex, neurons are surrounded by specific microenvironments containing extracellular molecules such as neurotrophins [brain-derived neurotrophic factor (BDNF) and neurotrophin 3 (NT3)], insulin-like growth factor 1 (IGF1), Wnt5A, transforming growth factor-β (TGF-β) and Semaphorin 3A, and cell adhesion molecules such as TAG1 and N-cadherin, which provide cues for neuronal polarization (Figure 2A; Funahashi et al, 2014; Namba et al, 2015; Takano et al, 2015; Rozes-Salvador et al, 2018). Indeed, inhibition of neurotrophin receptors, TrkB and TrkC, block the MP-to-BP transition in vivo (Nakamuta et al, 2011).…”
Section: Extrinsic Signaling In Axon and Dendrite Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing cortex, neurons are surrounded by specific microenvironments containing extracellular molecules such as neurotrophins [brain-derived neurotrophic factor (BDNF) and neurotrophin 3 (NT3)], insulin-like growth factor 1 (IGF1), Wnt5A, transforming growth factor-β (TGF-β) and Semaphorin 3A, and cell adhesion molecules such as TAG1 and N-cadherin, which provide cues for neuronal polarization (Figure 2A; Funahashi et al, 2014; Namba et al, 2015; Takano et al, 2015; Rozes-Salvador et al, 2018). Indeed, inhibition of neurotrophin receptors, TrkB and TrkC, block the MP-to-BP transition in vivo (Nakamuta et al, 2011).…”
Section: Extrinsic Signaling In Axon and Dendrite Specificationmentioning
confidence: 99%
“…The phospho-mimic mutant of Par3, which cannot bind to KIF3A, failed to rescue the knockdown phenotype, indicating that the accumulation of Par3 in the nascent axon is essential for MP-to-BP transition in vivo (Funahashi et al, 2013). Par6 also colocalizes with the TGF-β receptor (TβR2) and the phosphorylation of Par6 at Ser345 by the TGF-β receptor regulates axon formation and neuronal migration (Ozdamar et al, 2005; Yi et al, 2010; Rozes-Salvador et al, 2018).…”
Section: Downstream Targets Of Positive Feedback Signalsmentioning
confidence: 99%
“…C-terminal SxS motif (Ser 423/425 and Ser 465,467 for SMAD3 and SMAD2, respectively) (Matsuzaki, 2013). While early models suggested that SMAD2 interacts with the SMAD binding domain (SBD) of the SMAD anchor for receptor activation (SARA) followed by SARA:SMAD2 delivery to the TGF-βRI via the C-terminal domain of SARA to facilitate R-SMAD phosphorylation, the actual involvement of SARA in TGF-β signaling is controversial (Rozés-Salvador et al, 2018. Regardless of the precise mechanism, pR-SMADs complex with the shuttle SMAD4 and translocate to the nucleus to impact transcription of a rather large slate of TGF-β1 responsive genes (Massagué, 2000;Massague, 2012).…”
Section: Involvement Of P53 In Tgf-β1-induced Renal Fibrosismentioning
confidence: 99%
“…The role played by this protein in TGFRs trafficking and TGFβ1 signaling remains controversial, and its expression tends to decrease in liver fibrosis. All these aspects have been recently reviewed by Rozés-Salvador et al in [58].…”
Section: Agap2 In Tgfβ Receptor Traffickingmentioning
confidence: 99%